MECHANISM FOR TRANSFERRING THE RESOLUTION OF INDUSTRIAL RELATIONS DISPUTES THROUGH MEDIATION FROM THE NORTH LOMBOK REGENCY LABOR OFFICE TO THE WEST NUSA TENGGARA PROVINCIAL LABOR OFFICE - Kusuma, Rahmawati; Asyhadie, Zaeni (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
This study aims to understand about the mechanism for transferring the resolution of disputes through mediation from the North Lombok Regency Labor Office to the West Nusa Tenggara Provincial Labor Office. The issues addressed in this study are why dispute resolution through mediation must be transferred to the NTB Provincial Labor Office and how the transfer mechanism works. The research method used in this study is Normative-Empirical Legal Research, which combines normative legal elements with additional empirical data. The findings of the research indicate that the main factor leading to the transfer of industrial relations disputes from the regency to the province is the absence of a mediator in North Lombok Regency. As a result, the parties involved can be referred to the provincial government, which has mediators. There is no specific mechanism for the transfer of such cases; the labor office merely sends a request letter to assign a mediator to handle the industrial relations issues through mediation. It is hoped that the central government can appoint or assign a mediator to be placed in the region to avoid the need for case transfers from the regency to the province, thereby minimizing the time required to resolve ongoing industrial relations disputes.